2011
DOI: 10.1128/cvi.00390-10
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Plasmid DNA Vaccine Antigen Clearance by Caspase 12 RNA Interference Potentiates Vaccination

Abstract: The magnitude of the immune responses elicited by plasmid DNA vaccines might be limited, in part, by the duration of vaccine antigen expression in vivo. To explore strategies for improving plasmid DNA vaccine efficacy, we studied the apoptotic process in myocytes of mice vaccinated intramuscularly. We found that after vaccination, the proapoptotic protein caspase 12 (Casp12) was upregulated in myocytes coincident with the loss of vaccine antigen expression. To harness this observation to improve plasmid DNA va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…For example, immune responses induced by DNA vaccines are attenuated due to the limited duration of antigen expression in vivo. Due to death of transfected cells, use of shRNA to knock down caspase 12 (Casp12), a cell death mediator that is upregulated after DNA vaccination resulted in increased plasmid luciferase and HIV-gp120 Env antigen expression and higher CD8 T cell and antibody production (Geiben-Lynn et al, 2011). Similarly, RNAi-mediated depletion of the pro-apoptotic proteins Bak and Bax at the time of immunization of HPV16 E7 vaccine prolonged the life of antigen-expressing DCs and increased antitumor effects against E7-expressing tumors (Kim et al, 2005).…”
Section: Rnai Technologies In Dna Vaccine Designmentioning
confidence: 99%
“…For example, immune responses induced by DNA vaccines are attenuated due to the limited duration of antigen expression in vivo. Due to death of transfected cells, use of shRNA to knock down caspase 12 (Casp12), a cell death mediator that is upregulated after DNA vaccination resulted in increased plasmid luciferase and HIV-gp120 Env antigen expression and higher CD8 T cell and antibody production (Geiben-Lynn et al, 2011). Similarly, RNAi-mediated depletion of the pro-apoptotic proteins Bak and Bax at the time of immunization of HPV16 E7 vaccine prolonged the life of antigen-expressing DCs and increased antitumor effects against E7-expressing tumors (Kim et al, 2005).…”
Section: Rnai Technologies In Dna Vaccine Designmentioning
confidence: 99%
“…In this case, the in vivo silence of FOXO3 was responsible for increasing the frequency of tumor‐specific CD8 + T cells and for inhibiting tumor growth 41 . Other studies have also shown that the co‐administration of shRNA‐expressing plasmids targeting Caspase 12 and Fas ligand improved DNA vaccine immunogenicity 42 , 43 . We understand that constitutive APOBEC2 expression may have impaired our approach of being more effective and believe that adjuvant formulations including APOBEC2 blockers should be considered as a complementary strategy to improve DNA vaccine immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi can be used to down-regulate genes that suppress DNA vaccine action. For example, use of shRNA to knock down caspase 12, a cell death mediator that is upregulated after DNA vaccination, increased plasmid gene expression and T-cell and antibody responses [113]. Similarly, depletion by RNAi of Foxo3, a critical suppressive regulator of T cell proliferation, increased the efficacy of a HER-2/neu cancer vaccine [114].…”
Section: Shrna or Sirna As Molecular Adjuvantsmentioning
confidence: 99%
“…shRNA or siRNA targeting certain regulatory genes, e.g. caspase 12 [113], Foxo3 [114], PD-L1 [116] and IL-10 [117] shown to have adjuvant effects. RNAi against APOBEC enhanced DNA vaccine immunogenicity [119].…”
Section: Removal Of Bacterial Elementmentioning
confidence: 99%